Millennial Generation Religious Moderation Pusian Youth Organization Based on The 1945 Constitution Post Amendment to Article 28E Paragraph 1 - Agustien Cherly Wereh; Leidy Wendy Palempung; Reynold Simanjuntak; Merry Lenda Kumajas; Henry Lumenta; Romi Mesra (Ideas Publishing, 2023)
Religious moderation is a component of character education, and religious moderation is a government strategy that is beneficial for reconciling religious differences. Religious moderation is used to mitigate disparities between religious groups. The aim of this research is to find out how the millennial generation religious moderation pusian youth organization based on the 1945 constitution post amendment to article 28E paragraph 1. This research uses qualitative research methods with data collection methods in the form of observation, interviews, and taking documentation. The data analysis used in this research is in the form of data reduction, then how the data is presented, until then the data is drawn to a conclusion. This research can be concluded as, collaboration between youth organizations of different religions, increasing internal and external social awareness of youth organization, increasing the worship activities of youth organization, and youth organization community service work with the surrounding community.